Searching for nuclear stellar discs in simulations of star cluster mergers - Portaluri, Elisa; Corsini, E. M.; Morelli, L.; Hartmann, Maximilian; Dalla Bontà, E.; Debattista, Victor P.; Pizzella, A. (Monthly notices of the Royal Astronomical Society, 2013)
The nuclei of galaxies often host small stellar discs with scalelengths of a few tens of parsecs and luminosities up to 107 L⊙. To investigate the formation and properties of nuclear stellar discs (NSDs), we look for their presence in a set of N-body simulations studying the dissipationless merging of multiple star clusters in galactic nuclei. A few tens of star clusters with sizes and masses comparable to those of globular clusters observed in the Milky Way are accreted on to a pre-existing nuclear stellar component: either a massive super star cluster or a rapidly rotating, compact disc with a scalelength of a few parsecs, mimicking the variety of observed nuclear structures. Images and kinematic maps of the simulation time-steps are then built and analysed as if they were real and at the distance of the Virgo cluster. We use the Scorza-Bender method to search for the presence of disc structures via photometric decomposition. In one case, the merger remnant has all the observed photometric and kinematic properties of NSDs observed in real galaxies. This shows that current observations are consistent with most of the NSD mass being assembled from the migration and accretion of star clusters into the galactic centre. In the other simulation instead, we detect an elongated structure from the unsharp masked image, that does not develop the photometric or kinematic signature of an NSD. Thus, in the context of searches for a disc structure, the Scorza-Bender method is a robust and necessary tool.